Amniotic mesenchymal cells from pre‐eclamptic placentae maintain immunomodulatory features as healthy controls. Issue 1 (30th October 2015) - Pianta, Stefano; Magatti, Marta; Vertua, Elsa; Bonassi Signoroni, Patrizia; Muradore, Ivan; Nuzzo, Anna Maria; Rolfo, Alessandro; Silini, Antonietta; Quaglia, Federico; Todros, Tullia; Parolini, Ornella
Abstract: Pre‐eclampsia (PE) is one of the most severe syndromes in human pregnancy, and the underlying mechanisms of PE have yet to be determined. Pre‐eclampsia is characterized by the alteration of the immune system's activation status, an increase in inflammatory Th1/Th17/APC cells, and a decrease in Th2/Treg subsets/cytokines. Moreover, inflammatory infiltrates have been detected in the amniotic membranes of pre‐eclamptic placentae, and to this date limited data are available regarding the role of amniotic membrane cells in PE. Interestingly, we and others have previously shown that human amniotic mesenchymal stromal cells (hAMSC) possess anti‐inflammatory properties towards almost all immune cells described to be altered in PE. In this study we investigated whether the immunomodulatory properties of hAMSC were altered in PE. We performed a comprehensive study of cell phenotype and investigated the in vitro immunomodulatory properties of hAMSC isolated from pre‐eclamptic pregnancies (PE‐hAMSC), comparing them to hAMSC from normal pregnancies (N‐hAMSC). We demonstrate that PE‐hAMSC inhibit CD4/CD8 T‐cell proliferation, suppress Th1/Th2/Th17 polarization, induce Treg and block dendritic cells and M1 differentiation switching them to M2 cells. Notably, PE‐hAMSC generated a more prominent induction of Treg and higher suppression of interferon‐γ when compared to N‐hAMSC, and this was associated with higher transforming growth factor‐β1 secretion and PD‐L2/PD‐L1 expression in PE‐hAMSC. In conclusion, for the first time we demonstrate that there is no intrinsic impairment of the immunomodulatory features of PE‐hAMSC. Our results suggest that amniotic mesenchymal stromal cells do not contribute to the disease, but conversely, could participate in offsetting the inflammatory environment which characterizes PE.